1980
DOI: 10.1161/01.str.11.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in regional cerebral blood flow during normal aging in man.

Abstract: SUMMARY Regional cerebral blood flow (rCBF) was measured by the '"Xenon inhalation method in a selected group of 44 normal non-hospitalized, normotensive subjects aged 19 to 79 years. rCBF was computed as the initial slope index value (ISI). Advancing age was associated with significant reductions in the mean brain and mean hemispheric ISI as well as in individual ISI levels measured from all areas in both hemispheres. Our findings suggest that decline of rCBF is not limited to normal elderly subjects but that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
105
2
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(122 citation statements)
references
References 21 publications
13
105
2
1
Order By: Relevance
“…This indication of frontal dys function is interesting to relate to the findings of Te rry et al (1987), who found a significant shrinkage of large neurons together with a decre-ment in the neuron-glia ratio in midfrontal and su perior temporal areas in normal aged brains. These results thus support the suggestion by Melamed et al (1980) that the age-related reduction in frontal blood flow is related to neuronal loss.…”
Section: Regional Distribution Valuessupporting
confidence: 91%
“…This indication of frontal dys function is interesting to relate to the findings of Te rry et al (1987), who found a significant shrinkage of large neurons together with a decre-ment in the neuron-glia ratio in midfrontal and su perior temporal areas in normal aged brains. These results thus support the suggestion by Melamed et al (1980) that the age-related reduction in frontal blood flow is related to neuronal loss.…”
Section: Regional Distribution Valuessupporting
confidence: 91%
“…The infl uence of age on cerebral blood fl ow parameters is a well-known phenomenon (Naritomi et al 1979;Melamed et al 1980). The decline in cerebral blood fl ow with advancing age may be associated with certain changes in cerebrovascular hemodynamics such as decreased metabolic demands, higher hematocrit and lower partial pressure of carbon dioxide levels (Melamed et al 1980), vessel-size changes (Kusunoki et al 1999), and lower cardiac output (Safar 1990).…”
Section: Discussionmentioning
confidence: 99%
“…While some studies reported no gender differences in CBF (Melamed et al, 1980;Hannay et al, 1983), others found that women had higher rates of CBF than men and that was related to age, since by the sixth decade (Gur et al, 1987) men and women had similar flow rates. PET (Rodriguez et al, 1988;Gur and Gur, 1990;Jaeger et al, 1998;Ragland et al, 2000) and fMRI (Kastrup et al, 1999) studies found differences in activation during resting state (Rodriguez et al, 1988), cognitive tasks (Gur and Gur, 1990;Jaeger et al, 1998;Ragland et al, 2000), or visual stimulation (Kastrup et al, 1999).…”
Section: Gender Differences In Activationmentioning
confidence: 94%